ANALISA APLIKASI MANAJEMEN LAPORAN KEUANGAN MASJID BERBASIS TEKNOLOGI INFORMASI ANDROID TERHADAP PENERAPAN MUAMALAH SYARIAH - Ahmad Nabil (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
This research analyzes an Android-based information technology application for managing mosque financial reports in the context of Shariah-compliant transactions. The integration of information technology in mosque financial management aims to enhance transparency, accountability, and adherence to Shariah principles. The study involves surveys, observations, and a comprehensive analysis of the application developed to facilitate financial recording and reporting in accordance with Shariah principles. Accurate and transparent financial record-keeping is an integral part of Shariah-compliant transactions, and this application is designed to simplify the management and reporting of mosque funds. The analysis results indicate that the Android-based mosque financial report management application contributes positively to the implementation of Shariah principles. With features such as income and expenditure recording, donation tracking, and easily accessible financial reports, this application assists mosque administrators in managing funds in accordance with Shariah principles. The application's implementation also yields benefits in terms of time efficiency and accuracy in financial reporting, reducing errors that might occur in manual records. Moreover, enhanced transparency through this technology can reinforce the congregation's trust in the management of mosque funds in line with Shariah principles. The Android-based mosque financial report management application can be an effective tool in supporting the implementation of Shariah principles. However, regular monitoring and evaluation are necessary to ensure the application's compliance with relevant Shariah principles and its maximal adoption by mosque administrators.